Dosis y momento de aplicación de abono liquido (biol) en el cultivo de cebolla china (allium fistulosum) variedad criolla en la localidad de lamas – San Martín, Perú - Gallegos Mendoza, Sergio Maximiliano (2010)
The present work titled Dose and moment of application of the fertilizer (Biol) in the culture of chinese onion (Allium fistulosum) creole variety in the locality of Lamas – San Martín, Perú it has as objectives: To compare Biol’s different doses applied to the foliage and his effect on the growth and production of chinese onion, like that like to determine the ideal moment of Biol’s application to obtain better performances in the culture of chinese onion. The work of investigation I carry out specially in the country property of the Ing. Jorge Luis Pelaez Rivera, located in the Killoalpa sector, district and province of Lamas. Located geographically: south latitude 06º20’15’’, length west 76º30’45’’, and an altitude of 814 m.s.n.m.m. I use a design in complete block at random or randomized, with arrangement factorial 4 x 4 with 17 treatments (included the witness) and three repetitions. The treatment T5 it showed the best behavior represented in the best parameters of weight of plant, height of plant and minor incident of undergrowths and diseases, due mainly to the favorable environmental conditions for their development and to the adaptability demonstrated to those conditions.